Comics and humor as a mode of government communication on public hygiene posters in Singapore. (April 2022) - Matwick, Keri; Matwick, Kelsi
Abstract: This paper analyzes national campaign comic posters as a government tactic to regulate social behavior. One of Singapore's first national campaigns, Keep Singapore Clean (1968) has continued in various reiterations, such as Keep Public Toilets Clean. From this particular campaign, four comic posters are found throughout the city-island's public toilets and provide instruction on social etiquette regarding the use of public toilets. Drawing upon sociopragmatic humor studies (Attardo, 2020; El-Arousy, 2007 ) and multimodal discourse analysis (Kress & Van Leeuwen, 2006 ), the comic posters are read as verbal-visual representations set within a specific sociopolitical context. Humor is shown throughout to serve as a powerful discursive strategy to educate the public and makes the content relatable, while addressing the taboo topic of bathroom business.